A unique olfactory bulb microcircuit driven by neurons expressing the precursor to glucagon-like peptide 1 - Thiebaud, Nicolas (Sci Rep, 2019)
The presence of large numbers of local interneurons in the olfactory bulb has demonstrated an extensive local signaling process, yet the identification and purpose of olfactory microcircuits is poorly explored. Because the discrimination of odors in a complex environment is highly dependent on the tuning of information by local interneurons, we studied for the first time the role of preproglucagon (PPG) neurons in the granule cell layer of the olfactory bulb. Combining electrophysiological recordings and confocal microscopy, we discovered that the PPG neurons are a population of cells expressing the precursor of glucagon-like peptide 1 and are glutamatergic; able to modulate the firing pattern of the mitral cells (M/TCs). Optogenetic activation of PPG neurons resulted in a mixed excitation and inhibition that created a multiphasic response shaping the M/TCs firing pattern. This suggests that PPG neurons could drive neuromodulation of the olfactory output and change the synaptic map regulating olfactory coding.